PENERAPAN E-MARKETING SEBAGAI MEDIA STRATEGI PENINGKATAN PENJUALAN DAN PENGEMBANGAN PASAR UKM DI KECAMATAN BATUI - Rahman, Wahyudin; Hadiyati, Rini; Belani, Sriwanti (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
This community service activity, titled Application of E-Marketing as a Strategy for Increasing Sales and Market Expansion for MSMEs in Batui District, aimed to empower MSME actors by introducing digital marketing strategies. Through a series of training and direct mentoring, participants learned to utilize social media platforms (Facebook, Instagram, and TikTok) and e-commerce marketplaces (Tokopedia, Bukalapak, Shopee) to expand their market reach. The training covered content creation, social media management, and using analytical tools to evaluate marketing campaign effectiveness. The results showed a significant increase in social media followers and online transactions. However, challenges were observed in adopting digital technologies, especially among older MSME actors. Ongoing support is essential for ensuring the sustainability of these improvements. Overall, the application of e-marketing has proven to be a key strategy for enhancing MSME competitiveness, enabling them to reach broader markets locally, nationally, and internationally